Adherence and optimization of angiotensin converting enzyme inhibitor/angiotensin II receptors blockers and beta‐blockers in patients hospitalized for acute heart failure. (4th March 2021) - Carubelli, Valentina; Lombardi, Carlo; Specchia, Claudia; Peveri, Giulia; Oriecuia, Chiara; Tomasoni, Daniela; Di Pasquale, Mattia; Inciardi, Riccardo; Garrafa, Emirena; Metra, Marco
Abstract: Aims: Treatment with angiotensin converting enzyme inhibitor (ACEi)/angiotensin II receptors blockers (ARBs) and beta‐blockers is frequently suboptimal at discharge in patients hospitalized for acute heart failure (AHF). We investigated the prognostic significance of medical treatment at discharge and its changes during hospitalization. Methods and results: In a retrospective analysis, we included 623 patients hospitalized for AHF with reduced left ventricular ejection fraction (<40%). The primary endpoint was all‐cause mortality and heart failure rehospitalization to Day 180 since hospital discharge. A total of 249 (42.4%) of patients received no ACEi/ARBs/BB or <50% target dose (TD) of these drugs, 249 (42.4%) had either ACEi/ARBs or BB ≥ 50% of TD, and 89 (15.2%) ACEi/ARBs and BB ≥ 50% of TD at discharge. The primary endpoint was significantly lower in patients receiving at least one drug ≥50% of TD compared with no or low‐dose treatment (ACEi/ARBs or BB ≥ 50% TD: adjusted hazard ratio (HR) 0.69, 95% confidence interval (CI) [0.49–0.98], P = 0.04; ACEi/ARBs and BB ≥ 50% TD: adjusted HR 0.54, 95% CI [0.30–0.96], P = 0.03). With regard to treatment changes from admission to discharge, therapy was decreased in 258 (44.6%) patients, stable in 194 (33.6%), and increased in 126 (21.8%). Compared with patients with stable therapy, treatment intensification was associated with a lower rate of the primary endpoint (adjusted HR 0.49, 95% CI [0.29–0.83]; P = 0.01). Conclusions: In patients with AHF, prescription of ACEi/ARBs/BB ≥ 50% TD at the time of discharge, whether achieved or not through treatment intensification during the hospitalization, is associated with better post‐discharge outcomes.